A solvothermal method for synthesizing monolayer protected amorphous calcium carbonate clusters. Issue 43 (10th May 2016) - Sun, Shengtong; Gebauer, Denis; Cölfen, Helmut
Abstract : A solvothermal method is developed to synthesize organic monolayer protected amorphous calcium carbonate clusters. Abstract : A solvothermal method was developed for synthesizing organic monolayer protected amorphous calcium carbonate clusters using 10, 12-pentacosadiynoic acid as ligand, ethanol as solvent and NaHCO3 decomposition as CO2 source, which can be extended to synthesize other monolayer protected mineral clusters.